2018
DOI: 10.1017/s0305000918000302
|View full text |Cite
|
Sign up to set email alerts
|

Does phonological distance impact quality of phonological representations? Evidence from Arabic diglossia

Abstract: The study tested the impact of the phonological distance between Spoken Arabic (SpA) and Standard Arabic (StA) on quality of phonological representations among kindergarten, first-, second-, and sixth-grade Arabic-speaking children (N = 120). A pronunciation accuracy judgment task targeted three types of StA words that varied in extent of phonological distance from their form in SpA: (a) identical words, with an identical lexical-phonological form in StA and SpA; (b) cognate words, with partially overlapping p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 70 publications
(106 reference statements)
2
24
0
Order By: Relevance
“…For example, Ibrahim et al (2014) found that 3rd and 4th grade children were slower reading MSA than Hebrew (see also Eviatar & Ibrahim, 2001; Ibrahim, Eviatar, & Aharon Peretz, 2007). Others have likewise shown that problems with phonological‐awareness tasks, short‐term memory tasks and reading and spelling persist in native Arabic‐speaking children throughout primary education (up to the age of 11 years, e.g., Azzam, 1993; Brosh & Attili, 2009; Ibrahim, 2011; Saiegh‐Haddad & Haj, 2018; Saiegh‐Haddad & Schiff, 2016; Schiff & Saiegh‐Haddad, 2018; Taha, 2017), even after those children have presumably attained some degree of fluency with MSA. These difficulties were particularly pronounced in Arabic children with specific language impairment (Saiegh‐Haddad & Ghawi‐Dakwar, 2017) and dyslexia (Schiff & Saiegh‐Haddad, 2017) and can include deficits in semantic and syntactic processing (Khamis‐Dakwar, Froud, & Gordon, 2012; Leikin, Ibrahim, & Eghbaria, 2013).…”
Section: The Arabic Language and Writing Systemmentioning
confidence: 98%
“…For example, Ibrahim et al (2014) found that 3rd and 4th grade children were slower reading MSA than Hebrew (see also Eviatar & Ibrahim, 2001; Ibrahim, Eviatar, & Aharon Peretz, 2007). Others have likewise shown that problems with phonological‐awareness tasks, short‐term memory tasks and reading and spelling persist in native Arabic‐speaking children throughout primary education (up to the age of 11 years, e.g., Azzam, 1993; Brosh & Attili, 2009; Ibrahim, 2011; Saiegh‐Haddad & Haj, 2018; Saiegh‐Haddad & Schiff, 2016; Schiff & Saiegh‐Haddad, 2018; Taha, 2017), even after those children have presumably attained some degree of fluency with MSA. These difficulties were particularly pronounced in Arabic children with specific language impairment (Saiegh‐Haddad & Ghawi‐Dakwar, 2017) and dyslexia (Schiff & Saiegh‐Haddad, 2017) and can include deficits in semantic and syntactic processing (Khamis‐Dakwar, Froud, & Gordon, 2012; Leikin, Ibrahim, & Eghbaria, 2013).…”
Section: The Arabic Language and Writing Systemmentioning
confidence: 98%
“…Formal and direct exposure to literary Arabic occurs in parallel to the initial acquisition of reading and writing when the child begins school (Makhoul et al, 2015;Schiff & Saiegh-Haddad, 2018). However, young preschoolers are exposed to literary Arabic, usually indirectly, mainly through stories, songs, rhymes, TV programs, and printed matter at home (books, computer keyboards) and in public spaces (e.g., advertisement boards; Khamis-Dakwar, 2007;Leikin et al, 2014;Saiegh-Haddad & Everatt, 2017). This exposure to MSA has been suggested to be poor both in quality and quantity (Saiegh-Haddad, 2003.…”
Section: Potential Benefits For Early Exposure To Oral Languagementioning
confidence: 99%
“…This exposure to MSA has been suggested to be poor both in quality and quantity (Saiegh-Haddad, 2003. In the Israeli preschool (ages 3 to 6) curriculum (Ministry of Education, 2008), the starting point for developing basic literacy skills in Arabic is the spoken language (Saiegh-Haddad & Everatt, 2017). The implementation of MSA is not mandatory, and it is mainly recommended in the context of practical activities aimed to introduce and practice letter naming in MSA.…”
Section: Potential Benefits For Early Exposure To Oral Languagementioning
confidence: 99%
See 2 more Smart Citations